Gut microbiome response to short‐term dietary interventions in reactive hypoglycemia subjects. Issue 8 (15th September 2017) - Quercia, Sara; Turroni, Silvia; Fiori, Jessica; Soverini, Matteo; Rampelli, Simone; Biagi, Elena; Castagnetti, Andrea; Consolandi, Clarissa; Severgnini, Marco; Pianesi, Mario; Fallucca, Francesco; Pozzilli, Paolo; et al.
Abstract: Background: Reactive hypoglycemia is a metabolic disorder that provokes severe hypoglycemic episodes after meals. Over recent years, the gut microbiota has been recognized as potential target for the control of metabolic diseases, and the possibility to correct gut microbiota dysbioses through diet, favouring the recovery of metabolic homeostasis, has been considered. Methods: We investigate the impact of 2 short‐term (3‐day) nutritional interventions, based on the macrobiotic Ma‐Pi 2 diet and a control Mediterranean diet, on the structure and functionality of the gut microbiota in 12 patients affected by reactive hypoglycemia. The gut microbiota composition was characterized by next‐generation sequencing of the V3 to V4 region of the 16S rRNA gene, and the ecosystem functionality was addressed by measuring the faecal concentration of short‐chain fatty acids (SCFAs). In order to measure the short‐term physiological gut microbiota fluctuation, the microbiomes of 7 healthy people were characterized before and after 3 days of constant diet. Results: While no convergence of the gut microbiota compositional profiles was observed, a significant increase in SCFA faecal levels was induced only in the Ma‐Pi 2 diet group, suggesting the potential of this diet to support a short‐term functional convergence of the gut microbiota, regardless of the individual compositional layout. Conclusions: The Ma‐Pi 2 diet, with its high fibre load, was effective in increasing the production of SCFAs by the gut microbiota. Because these metabolites are known for their ability to counterbalance the metabolic deregulation in persons with glucose impairment disorders, their increased bioavailability could be of some relevance in reactive hypoglycemia.